FORUM EKSPERTÓWNeochordae as the primary technique for repair of isolated posterior mitral leaflet prolapse: a comparison to traditional techniques - Yusuf, Meeranghani M.; Luckraz, Heyman; Szafranek, Adam; Vintilla, Vlad; Masani, Navroz; Fraser, Alan G.; Von Oppell, Ulrich (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Aim: Posterior mitral valve leaflet (PMVL) prolapse repair using CV5 Gore-Tex neochordae without leaflet resection used as the primary method of repair was compared to traditional quadrangular leaflet resection. Material and methods: Prospective data were collected in 186 consecutive mitral valve repair patients; January 2003 to March 2006. Bi-leaflet repairs were required in 63 and PMVL only in 54. The latter group formed the study group; 23 patients underwent repair using neochordae prepared to specific intraoperative measurements using a single suture technique and an annuloplasty ring without any resection (group I). The remaining 31 patients underwent more traditional quadrangular resection and an annuloplasty ring (group II). We compared immediate and short-term results between these groups. Results: Preoperative mitral regurgitation was severe in 87% (20/23) and 94% (29/31) respectively. Ten patients in group I (43%) and 2 patients in group II (6%) had prolapse of more than one posterior leaflet segment. Combined CABG was performed in 35% and 42% of patients respectively. Intraoperative post-repair transoesophageal echocardiography revealed trivial or less residual regurgitation in all patients in group I and 94% of group II. At follow-up (FU) 100% of the patients in group 1 (median FU 12.9 months) and 81% in group II (median FU 24.3 months) were in NYHA class 1 (p<0.05). Transthoracic echocardiography FU revealed trivial or no mitral regurgitation in group I – 82% and group II – 56% (P=0.11). There was one operative death in group II and 1 late death in each group. Conclusions: Gore-Tex neochordae used as the primary repair technique for PMVL prolapse is reproducible and shows comparable and possibly superior results to traditional quadrangular resection/reconstruction repair.